The English Vocabulary Acquisition of the Students of State Junior High School 2 Parepare - Rafiqa Rafiqa (Universitas Sulawesi Barat, 2017)
The Objective of the research: to get information about the English vocabulary acquisition of the seventh, the eight and the ninth grade of students of state junior high school 2 Parepare. The researcher applied cross-sectional design to investigate differences between participants that vary by grade. The research population were all pupils who learned English, so the population of this research were students of State Junior High School 2 Parepare. They are the seventh grade which consist of 210 students, eight grade which consist of 208 students, and ninth grade consist of 234 students. The total number of population are 652.The researcher took sample from each grade by using random sampling technique. At the seventh grade consist of 36 students, at the ninth grade consist of 34 students, and the ninth grade consist of 32 students, so total number of sample are 102. The result of this research showed that mean score of each grade were different. Mean score of seventh grade were 6,0778, it was lower than eight grade and ninth grade. Mean score of eight grade were 8,1088 means that it was in the middle between seventh and ninth group. And then mean score at ninth grade were 9,2500, it was a higher mean score than eight grade and seventh grade. Based on mean score from students of each grade showed that students of higher grade would they have higher vocabulary size.